HUBUNGAN KONSUMSI ZAT GIZI, PERSENTASE LEMAK TUBUH DAN AKTIVITAS FISIK DENGAN KEBUGARAN JASMANI PADA ATLET RENANG - Karinta Ariani Setiaputri; M. Zen Rahfiludin; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Physical fitness is the ability to do daily activities effectively and efficiently. Nutritional requirements are important for athletes since their energy requirements are higher than non athletes, especially in children athletes whose their nutritional needs also used in their growth. Athletes's physical activity requires more energy intake to create optimal physical fitness. The purpose of this research was to determine the correlation of nutritional intake, body fat percentage and physical activity with physical fitness in swimming athlete. The type of this research was explanatory research approach with cross sectional design. The population were all the swimming athletes who are 13-18 years old in PPLOP and TCS Swimming Club. The sample were taken by using purposive sampling technique. Data was analyzed using Pearson Product Moment and Rank Spearman. The result showed that level of energy consumption was classified as adequate (50%). Level of fat consumption was good (53,3%). Body fat percentage was normal (66,7%). Physical activity was heavy (40%). Physical fitness moderate (60%). The result of this research showed that there were no correlation between level of energy consumption (p = 0,269) and level of fat consumption (p = 0,054) with physical fitness in swimming athletes. There was correlation between physical activity (p = 0,006) with physical fitness in swimming athletes, but no correlation between body fat percentage (p = 0,066) with physical fitness in swimming athletes. This research recommended athletes to increase their energy consumption in order to fulfill their nutritional needs, moreover athletes's physical fitness should also be improved to increase athletes's performance during excercise and competition.